Differences between genotypic and phenotypic resistance in MDR-TB strains in South Africa - Sewpersadh, Mandira (My University, 2013)
South Africa (SA) is burdened with one of the highest tuberculosis (TB) infection rates worldwide. The dual epidemic of HIV and MDR- and extensively drug-resistant (XDR) -TB outbreaks prompted the World Health Organisation to call for a new rapid molecular diagnostics tool(s). To curb the spread of drug-resistant TB, SA introduced genotypic Hain MTBDRplus line probe assays (Hain LPA) for the routine rapid diagnosis of MDR-TB. This study aimed to determine the frequency, geographic distribution and genetic basis for phenotypic and genotypic drug susceptibility testing (DST) discordant findings. The cultures used in this study were isolated during the period June 2007- July 2008 from Western Cape, Gauteng, KwaZulu-Natal, and Northern Cape. A total of 118 comparable MGIT and Hain LPA DST were obtained with 41 isolates verified to be discordant. The predominant families were the LAM, T, X and, S. Hain LPA failed to identify INH resistance (R) in 46.3% (19/41) of isolates with MIC‟s supporting the phenotypic resistance. Genotypic RIF-R was shown in 31.7% (13/41) of isolates which was not expressed phenotypically but interestingly the MIC‟s favour the LPA resistance. Sequencing analysis of the rpoB gene region identified new mutations; Leu458Pro, Leu436Pro, and Asp441Gly, associated with missing wildtypes. For INH, the katG and inhA gene regions were sequenced. Mutations at codon Gly213Val, Pro232Lys, Lys254Asn, and Ser259Asn were detected in katG and a variety found in inhA. These mutations have not been previously reported neither are they incorporated on the Hain LPA strips. Detailed knowledge of the frequency distribution of resistance-linked mutations and associated MICs in different regions of SA, could facilitate understanding of the limitations of current molecular tests and inform testing algorithms. These findings impact on the use of new molecular diagnostics as well as epidemiological monitoring of drug-resistant strains.
Keywords: Tuberculosis, Multidrug-Rersistant